UNIVERSITY LIBRARY AS AN ZONE OF COMMUNICATIVE COMFORT - Ledenyeva, Nataliia D. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
In this scientific research discusses about university library as one of the teachers of harmonious and morally perfect university individuals.